FINANCIAL LITERACY LEVEL OF UNDERGRADUATE STUDENTS IN NUSA TENGGARA TIMUR - Lejap, Hedwigh Hendrikus Temai (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2022)
The purpose of this research is to see the level of financial literacy, financial attitude, financial behavior, and financial knowledge based on the socio-demographic factors of undergraduate students in Nusa Tenggara Timur Province. This research was conducted at three universities, namely Universitas Nusa Cendana (Undana), Universitas Timor (Unimor), and Universitas Katolik Widya Mandira (Unwira). The sample in this study were 328 students. While the data was collected using a questionnaire via Google form for approximately a month. The data were then analyzed using SPSS 21 to see the results of logistic regression and crosstab. The results showed that students in East Nusa Tenggara had a high level of financial attitude. Furthermore, financial literacy and financial behavior is at a low level. While the level of financial knowledge is at lowest level.